1999
DOI: 10.1016/s1352-8661(99)00049-6
|View full text |Cite
|
Sign up to set email alerts
|

Single breath-hold slice-following CSPAMM myocardial tagging

Abstract: Myocardial tagging has shown to be a useful magnetic resonance modality for the assessment and quantification of local myocardial function. Many myocardial tagging techniques suffer from a rapid fading of the tags, restricting their application mainly to systolic phases of the cardiac cycle. However, left ventricular diastolic dysfunction has been increasingly appreciated as a major cause of heart failure. Subtraction based slice-following CSPAMM myocardial tagging has shown to overcome limitations such as fad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 9 publications
2
47
0
Order By: Relevance
“…The use of variable flip angle without slice-following will in practice not produce a constant SNR unless the saturation effect of through-plane motion is taken into account. This may partly explain the slight increase in SNR over time seen in this study and previously [22]; however, some of this effect has also been observed using slice-following [3].…”
Section: Resultssupporting
confidence: 47%
See 2 more Smart Citations
“…The use of variable flip angle without slice-following will in practice not produce a constant SNR unless the saturation effect of through-plane motion is taken into account. This may partly explain the slight increase in SNR over time seen in this study and previously [22]; however, some of this effect has also been observed using slice-following [3].…”
Section: Resultssupporting
confidence: 47%
“…The flip angle optimization was based on heart rate, myocardial T 1 and excitation pattern, as previously reported [3]. T 1 values of 870 ms at 1.5T and 1114 ms at 3T were used.…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the RF pulses of the imaging sequence have significant effect on tag persistence (15,16). It is possible to improve SPAMM and CSPAMM tag persistence (contrast) by starting with a small flip angle when M Z is large and increasing the flip angle as M Z decreases (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to improve SPAMM and CSPAMM tag persistence (contrast) by starting with a small flip angle when M Z is large and increasing the flip angle as M Z decreases (15,16). Although we do not currently have the ability to use variable flip angles in cardiac gated cine imaging on our Marconi 1.5T Eclipse, we will be performing simulations to examine the effect of variable flip angles on MICSR contrast.…”
Section: Discussionmentioning
confidence: 99%